Implementasi Ethereum Blockchain dan Smart Contract Pada Jaringan Smart Energy Meter - Mabruroh, Anggun Mugi; Dewanta, Favian; Wardana, Aulia Arif (POLITEKNIK NEGERI JAKARTA, 2021)
In this study, we propose the creation of an Internet of Things device, namely a smart energy meter by implementing a blockchain system as a database. Internet of Things has a centralized storage system on the database server, if the server is down then the database cannot be used and data may be lost. There is a storage system that has a decentralized and distributed network, namely the blockchain. The private blockchain system is built using the Ethereum framework. Sensor data will be read by the Raspberry Pi 4B and sent to node 1 via MQTT. Node 1 will save the data to the block. Two nodes Ethereum account will validate the block. If accepted then the block will be stored on the blockchain and create a new block chain. In the storage process, there is a smart contract between Ethereum accounts that is created using Solidity and accessed using the web3 API. Successfully saved data will be displayed to the user's web. Based on the results of measuring the performance of the MQTT protocol and blockchain system when compared to traditional databases, blockchain is less fast in the storage process because there is a transaction process and data verification. However, if it is applied to smart energy meter data, it doesn't matter because the time required for the storage process is a maximum of 1 minute. The number of nodes and the size of the data or block does not affect the performance of the proof of authority consensus algorithm